Iron Excess Disturbs Metabolic Status and Relative Gonad Mass in Rats on High Fat, Fructose, and Salt Diets - Suliburska, Joanna (Humana Press Inc, 2012)
The aim of this study was to assess the metabolic and physiological changes in rats fed a diet high in fat, fructose, and salt, and with excess iron level. Mineral status was also estimated. Wistar rats were assigned to groups fed either a standard control diet (C) or a diet high in fat, fructose, and salt. The noncontrol diets contained either normal (M) or high level (MFe) of iron. After 6 weeks, the length and weight of the rats were measured, and the animals were euthanized. The kidneys and gonads were collected, and blood samples were taken. Serum levels of insulin, nitric oxide, and iron were measured. The iron, zinc, copper, and calcium concentrations of tissues were determined. It was found that the M diet led to a significant increase in the relative kidney mass of the rats compared with the control group. Among the rats fed the M diet, markedly higher serum level of iron and lower levels of zinc and copper were observed in tissues, while significantly higher calcium levels were found in the gonads. The MFe diet resulted in decreased obesity index, insulin level, and nitric oxide serum concentration in the rats, when compared with both the M and C diets. The high iron level in the modified diet increased the relative mass of the gonads. The excess iron level in the diet disturbed the zinc, copper, and calcium status of tissues. The decrease in insulin and nitric oxide in rats fed the diet high in iron, fat, fructose, and salt was associated with disorders of zinc, copper, and calcium status, as well as with an increase in the relative mass of the gonads.